Energy Harvesting from Sugarcane Bagasse Juice using Yeast Microbial Fuel Cell Technology - Marcelinus Christwardana; Linda Aliffia Yoshi; J. Joelianingsih (Reaktor, 2021)
This study demonstrates the feasibility of producing bioelectricity utilizing yeast microbial fuel cell (MFC) technology with sugarcane bagasse juice as a substrate. Yeast Saccharomyces cerevisiae was employed as a bio-catalyst in the production of electrical energy. Sugarcane bagasse juice can be used as a substrate in MFC yeast because of its relatively high sugar content. When yeast was used as a biocatalyst, and Yeast Extract, Peptone, D-Glucose (YPD) Medium was used as a substrate in the MFC in the acclimatization process, current density increased over time to reach 171.43 mA/m2 in closed circuit voltage (CCV), maximum power density (MPD) reached 13.38 mW/m2 after 21 days of the acclimatization process. When using sugarcane bagasse juice as a substrate, MPD reached 6.44 mW/m2 with a sugar concentration of about 5230 ppm. Whereas the sensitivity, maximum current density (Jmax), and apparent Michaelis-Menten constant (????????????????????) from the Michaelis-Menten plot were 0.01474 mA/(m2.ppm), 263.76 mA/m2, and 13594 ppm, respectively. These results indicate that bioelectricity can be produced from sugarcane bagasse juice by Saccharomyces cerevisiae.Keywords: biomass valorization, biofuel cell, acclimatization, maximum power density, Michaelis-Menten constant